IMPLEMENTASI FRAMEWORK COBIT 2019 PADA AUDIT TATA KELOLA SISTEM INFOMASI PADA DINAS PENANAMAN MODAL DAN PTSP KOTA X - Ni Luh Putu Yuliandri; I Gede Putu Krisna Juliharta; Ni Made Estiyanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Investment Service and PTSP City X information technology governance audit aims to map the maturity level of IT processes. Information system governance should be evaluated to determine the institution conditions regarding IT performance management to control quality. The framework is one that can assist in assessing the performance of the underlying information technology. The development of information system governance is supported by a governance information system framework. The audit in this study uses the 2019 COBIT framework which focuses on the use of IT systems, the maturity level of available services, and administrative services through information systems. Based on the maturity obtained, the EDM04, APO07, APO11, and DSS03 processes are carried out. The EDM04 process is at level 3 (established process), APO07 is at level 2 (managed process), APO11 is at level 2 (managed process), and DSS03 is at level 4 (predictable process) with an average capability gap of 2.25. The results of these procedures can be said that the services provided by Investment Service and PTSP City X have been carried out with largely achieved status, but not yet in the best condition, allowing for the implementation of suggestions and improvements as well as the level of ability to be measured again as a comparison tool.